Substance use policy and practice in the COVID-19 pandemic: Learning from early pandemic responses through internationally comparative field data. Issue 12 (2nd December 2022) - Aronowitz, Shoshana V.; Carroll, Jennifer J.; Hansen, Helena; Jauffret-Roustide, Marie; Parker, Caroline Mary; Suhail-Sindhu, Selena; Albizu-Garcia, Carmen; Alegria, Margarita; Arrendondo, Jaimie; Baldacchino, Alexander; Bluthenthal, Ricky; Bourgois, Philippe; et al.
ABSTRACT: The COVID-19 pandemic has created an unprecedented natural experiment in drug policy, treatment delivery, and harm reduction strategies by exposing wide variation in public health infrastructures and social safety nets around the world. Using qualitative data including ethnographic methods, questionnaires, and semi-structured interviews with people who use drugs (PWUD) and Delphi-method with experts from field sites spanning 13 different countries, this paper compares national responses to substance use during the first wave of the COVID-19 pandemic. Field data was collected by the Substance Use x COVID-19 (SU x COVID) Data Collaborative, an international network of social scientists, public health scientists, and community health practitioners convened to identify and contextualise health service delivery models and social protections that influence the health and wellbeing of PWUD during COVID-19. Findings suggest that countries with stronger social welfare systems pre-COVID introduced durable interventions targeting structural drivers of health. Countries with fragmented social service infrastructures implemented temporary initiatives for PWUD led by non-governmental organisations. The paper summarises the most successful early pandemic responses seen across countries and ends by calling for greater systemic investments in social protections for PWUD, diversion away from criminal-legal systems toward health interventions, and integrated harm reduction, treatment and recovery supports for PWUD.